ranslation of Holy Quran - م.د. محمود عبد الحسين الثعالبي ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The issue of translation of the Koran from the important issues and vitality that has stirred up controversy and disagreement among scientists in the modern between supporters and its shows the times, that they are not of the innovations era, but it is as old as the descent of the Holy Quran on the chest of the Prophet (Allah bless him and his family), and the first Who this is to translate any of the Koran is a great companion Salman Muhammadi (RIP) when translated verse basmalah to the Persian language and presented to the Prophet (Allah bless him and his family) these scientists believe it is one of the necessities of the Islamic Dawa and the delivery notification to all the nations of the earth and the establishment of the argument them where God sent His Messenger, the Qur'an to all people glad tidings and a harbinger, but the other part of refusing to translate the Koran under the pretext of breach of the meanings of the Qur'an and the performance of the Word in a language other than Arabic language because it is the word of God miraculous rude and meaning, and then the translation would be a distortion that were not in his words In a sense.